Unravelling the family-based haunted house film patterns in Malaysian and American haunted house films - Ahmad Muhyiddin Yusof,; Ruzy Suliza Hashim,; Noraini Md Yusof,; Anita Harris Satkunananthan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this article, we attempt to unravel the family-based haunted house film patterns in both Malaysia and America. Certain types of tropes and attributes have been used by horror filmmakers over the years to define the family motif-pattern of haunted houses in the media. Some of these elements have undergone change over time but most of them still adhere to the rules that constitute the family-based haunted house film patterns based on two Malay films and two American films. These rules were compared and contrasted by applying a combination of two theories which were formulated by Propp and Bailey. Application of these formulas has resulted in the findings of twelve plot functions as examined in this article. Upon analysis of the corpus, it has also been found that there are 10 existing attributes of a haunted house. The findings suggest that the haunted house film pattern is not merely a motif but it is also able to exhibit a number of themes which are considered prominent in haunted house films such as the Manichean clash between good and evil. The convergence and divergence between the Malaysian and American horror flicks show that cultural and religious practices govern the ways in which good and evil are expressed.